A universal framework for Space Resource Utilisation (SRU). (March 2020) - Hadler, K.; Martin, D.J.P.; Carpenter, J.; Cilliers, J.J.; Morse, A.; Starr, S.; Rasera, J.N.; Seweryn, K.; Reiss, P.; Meurisse, A.
Abstract: Space Resource Utilisation (SRU) or In Situ Resource Utilisation (ISRU) is the use of natural resources from the Moon, Mars and other bodies for use in situ or elsewhere in the Solar System. The implementation of SRU technologies will provide the breakthrough for humankind to explore further into space. A range of extraction processes to produce useable resources have been proposed, such as oxygen production from lunar regolith, extraction of lunar ice and construction of habitation by 3D printing. Practical and successful implementation of SRU requires that all the stages of the process flowsheet (excavation, beneficiation and extraction) are considered. This requires a complete 'mine-to-market' type approach, analogous to that of terrestrial mineral extraction. One of the key challenges is the unique cross-disciplinary nature of SRU; it integrates space systems, robotics, materials handling and beneficiation, and chemical process engineering. This is underpinned by knowledge of the lunar or planetary geology, including mineralogy, physical characteristics, and the variability in local materials. Combining such diverse fields in a coordinated way requires the use of a universal framework. The framework will enable integration of operations and comparison of technologies, and will define a global terminology to be used across all fields. In this paper, a universal SRU flowsheet and terminology are described, and a matrix approach to describing regolith characteristics specifically for SRU is proposed. This is the first time that such an approach has been taken to unify this rapidly-developing sector. Highlights: For SRU to progress towards implementation, integration between disciplines is required. The first step is to define a standard flowsheet and terminology. Terms such as yield, recovery and conversion are defined for SRU. A matrix for characterisation of regolith feedstock is developed.